PRACTICAL RELEVANCE OF STUDYING THE EFFECT OF STATINS ON THE EFFECTIVENESS OF TREATMENT OF PATIENTS WITH CHRONIC CORONARY HEART DISEASE WITH COVID-19 (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The pandemic of the new coronavirus infection COVID-19 and the quarantine measures that followed it, in particular, the self-isolation of the population, could seriously affect the quality of permanent pharmacotherapy (FT) and the adherence to it of patients with chronic non-communicable diseases. To determine the dynamics of adherence to continuous therapy in patients with chronic coronary heart disease (CHD) in self-isolation during the COVID-19 pandemic. In patients with stable coronary heart disease during the period of self-isolation during the COVID-19 pandemic and the associated lack of constant contact with the attending physician, a deterioration in adherence was revealed with an increase in the number of patients who stopped taking several or all prescribed drugs. The most pronounced negative dynamics was observed in adherence to disaggregants and statins. The leading barriers to adherence during the period of self-isolation were fear of side effects of LP and unwillingness to take large amounts of LP for a long time.